2021
DOI: 10.3389/fbuil.2021.640732
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Augmented Reality Applications in Civil Infrastructure During the 4th Industrial Revolution

Abstract: The 4th industrial revolution started in 2016 and referred to a new phase in the industrial revolution. One of the most significant technological evolvements during the 4th industrial revolution is Augmented Reality (AR) technology. AR superimposes interactional virtual objects/images to real environments. Because of the interaction and see-through characteristics, AR is better applied to engineering than Virtual Reality (VR). The application of AR in civil infrastructure can avoid artificial mistakes, improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 115 publications
(120 reference statements)
0
15
0
1
Order By: Relevance
“…is prompts us to further optimize and evaluate the relevant algorithms in the actual use process. e optimized algorithm has the characteristics of fast computing speed and small memory and can work well on a mobile platform, so as to meet the real-time requirements of augmented reality [19].…”
Section: Algorithm Description Of Augmented Realitymentioning
confidence: 99%
“…is prompts us to further optimize and evaluate the relevant algorithms in the actual use process. e optimized algorithm has the characteristics of fast computing speed and small memory and can work well on a mobile platform, so as to meet the real-time requirements of augmented reality [19].…”
Section: Algorithm Description Of Augmented Realitymentioning
confidence: 99%
“…It is also observed that while the available review studies in the literature are presented for different use cases in the AEC industry ( Figure 8 ), the authors of this paper did not identify any review or discussion study about the use of XR for condition assessment of civil engineering structures. A total of 25 literature review studies were identified that consider VR, AR, and MR separately [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], or VR and AR together [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], or VR, AR, and MR all together (which is XR) [ 61 , 62 ] in the AEC industry. Only two of these studies consider XR in their review, where they studied BIM in AEC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this study explores numerous strategies and approaches to value creation throughout IoT integrated with mixed reality in a manufacturing company to present the current perceptions and view the positive impacts and disruptions brought the application of the IoT integration with Mixed Reality on manufacturing operations of an organization. Besides, this study contributes to the discussion on the role of technologies in the manufacturing sector by providing empirical and framework evidence (Xu & Moreu, 2021). Thus, it will significantly help business organizations, especially the manufacturing sectors, to decide the kind of technology to use in their production system.…”
Section: Significance Of the Studymentioning
confidence: 92%
“…It keeps the organization about the condition, status, and location of the product. Such data are very useful for sensitive products such as drugs, perishable and fragile goods [10]. The types of information transmitted by integrated IoT with mixed reality technology are the usage data that state the frequency and how long the product is used or consumed by the customers.…”
Section: Data Visibilitymentioning
confidence: 99%